(Des)Qualificação dos trabalhadores do campo e da cidade: Cooperativa Central Aurora Alimentos, município de Xaxim, SC - Skrzypczak, Valdir (2020)
The western region of Santa Catarina is characterized, economically, by the presence of large agro-industrial groups, such as Brasil Foods (BRF) and Central Aurora Alimentos Cooperative, which have dominance on the meat sector and its derivatives, creating, in the integrated peasant family farmers, a strong dependency. In the class conflict and in the dialectical relation between the agro-industrial capital and field and city workers, these workers have been constantly qualifying themselves in order to meet the demands of capital production and reproduction, imposed by the agro-industry, which seeks to attend the national and international market. Following this logic, the workers improve their education/qualification, however, remain as employees in the agro-industry, which is constantly seeking to capture the subjectivity for the consensus and consent of the capitalist ways of production and reproduction, involving the proletarian in the web of relations concerning labor control, manipulation and overexploitation. Therefore, the general objective of this research is to comprehend how field and city workers are educated/(un)qualified to meet the interests of Central Aurora Alimentos Cooperative, one of the large agro-industrial groups in the western region of Santa Catarina. In this regard, the historical and dialectical materialism is applied in order to interpret the concrete reality analyzed, because this method constitutes, in essence, the bond of dialectic comprehension between the subject, represented by the peasant family farmers and by the agro-industry urban workers, and the object of this research, which is the (dis)qualification of these workers towards the agro-industrial capital. The delimited area for this investigation comprehends, thus, the city of Xaxim, in the western region of Santa Catarina, characterized by the presence of a poultry slaughterhouse that belongs to Central Aurora Alimentos Cooperative, and the period of study covers the years from 1980 to 2018, period characterized by significant transformations in the city and field spaces caused by the productive restructuring and the severe changes in the world of work and the global-scale production. In order to meet the proposed objective, we interviewed ten family farmers integrated in the poultry sector and ten employees of Central Aurora Alimentos Cooperative, the latter being students at CEJAX (Center of Youth and Adult Education of Xaxim), aiming to understand the relation between the (dis)qualification and the productive restructuring, from the simple and divided/partial work in the agro-industry. Based on that, it was observed that field and city workers have been constantly expanding their school education, however, they remain as employees in the agro-industry sector. Thus, CEJAX is oriented to the education of Central Aurora Alimentos Cooperative’s workers, but it does not emancipate/free them from the conditions of oppression and exploitation of paid and alienated labor inside the agro-industry. CEJAX educational training is oriented as a form of adaptation to the abilities and competences of the agro-industry polyvalent work, which has an education that is not a school education, based on the factory pedagogy and trainings. However, there is resistance, contraindications and transformations on the part of workers.